Impact of persistent PSA after salvage radical prostatectomy: a multicenter study - Preisser, Felix; Incesu, Reha-Baris; Rajwa, Pawel; Chlosta, Marcin; Nohe, Florian; Ahmed, Mohamed; Abreu, Andre Luis; Cacciamani, Giovanni; Ribeiro, Luis; Kretschmer, Alexander; Westhofen, Thilo; Smith, Joseph A; et al. (Prostate cancer and prostatic diseases, 2024)
BACKGROUND AND OBJECTIVE: Persistent prostatic specific antigen (PSA) represents a poor prognostic factor for recurrence after radical prostatectomy (RP). However, the impact of persistent PSA on oncologic outcomes in patients undergoing salvage RP is unknown. To investigate the impact of persistent PSA after salvage RP on long-term oncologic outcomes. MATERIAL AND METHODS: Patients who underwent salvage RP for recurrent prostate cancer between 2000 and 2021 were identified from twelve high-volume centers. Only patients with available PSA after salvage RP were included. Kaplan-Meier analyses and multivariable Cox regression models were used to test the effect of persistent PSA on biochemical recurrence (BCR), metastasis and any death after salvage RP. Persistent PSA was defined as a PSA-value ≥ 0.1 ng/ml, at first PSA-measurement after salvage RP. RESULTS: Overall, 580 patients were identified. Of those, 42% (n = 242) harbored persistent PSA. Median follow-up after salvage RP was 38 months, median time to salvage RP was 64 months and median time to first PSA after salvage RP was 2.2 months. At 84 months after salvage RP, BCR-free, metastasis-free, and overall survival was 6.6 vs. 59%, 71 vs. 88% and 77 vs. 94% for patients with persistent vs. undetectable PSA after salvage RP (all p < 0.01). In multivariable Cox models persistent PSA was an independent predictor for BCR (HR: 5.47, p < 0.001) and death (HR: 3.07, p < 0.01). CONCLUSION: Persistent PSA is common after salvage RP and represents an independent predictor for worse oncologic outcomes. Patients undergoing salvage RP should be closely monitored after surgery to identify those with persistent PSA.
Keywords: senioři; prostatektomie; Retrospective Studies; Prognosis; Middle Aged; mužské pohlaví; nádory prostaty; Salvage Therapy; Neoplasm Recurrence, Local; prostatický specifický antigen; lokální recidiva nádoru; Follow-Up Studies; Prostate-Specific Antigen; Biomarkers, Tumor; následné studie; prognóza; nádorové biomarkery; Prostatic Neoplasms; retrospektivní studie; Humans; záchranná terapie; Prostatectomy; lidé středního věku; Aged; lidé; Male